Plant selenium hyperaccumulation- Ecological effects and potential implications for selenium cycling and community structure - Reynolds, R. Jason B.; Pilon-Smits, Elizabeth A.H. (Biochimica et biophysica acta. General subjects, 2018)
Selenium (Se) hyperaccumulation occurs in ~50 plant taxa native to seleniferous soils in Western USA. Hyperaccumulator tissue Se levels, 1000–15,000 mg/kg dry weight, are typically 100 times higher than surrounding vegetation. Relative to other species, hyperaccumulators also transform Se more into organic forms. We review abiotic and biotic factors influencing soil Se distribution and bioavailability, soil being the source of the Se in hyperaccumulators. Next, we summarize the fate of Se in plants, particularly hyperaccumulators. We then extensively review the impact of plant Se accumulation on ecological interactions. Finally, we discuss the potential impact of Se hyperaccumulators on local community composition and Se cycling. Selenium (hyper)accumulation offers ecological advantages: protection from herbivores and pathogens and competitive advantage over other plants. The extreme Se levels in and around hyperaccumulators create a toxic environment for Se-sensitive ecological partners, while offering a niche for Se-resistant partners. Through these dual effects, hyperaccumulators may influence species composition in their local environment, as well as Se cycling. The implied effects of Se hyperaccumulation on community assembly and local Se cycling warrant further investigations into the contribution of hyperaccumulators and general terrestrial vegetation to global Se cycling and may serve as a case study for how trace elements influence ecological processes. Furthermore, understanding ecological implications of plant Se accumulation are vital for safe implementation of biofortification and phytoremediation, technologies increasingly implemented to battle Se deficiency and toxicity. •Selenium hyperaccumulators concentrate and transform Se within and around them.•Hyperaccumulation profoundly affects ecological interactions.•Hyperaccumulators may influence species composition and Se cycling.